Urban pollution. Cultural meanings, social practices. - (:unkn) unknown (Berghahn, 2010)
Das stadtethnologische Projekt "Wahrnehmung und kulturelle Deutung von 'Sauberkeit' und 'Schmutz' im Stadtraum"dessen Ergebnisse hier vorgestellt werden, untersucht kulturvergleichend die Wahrnehmungen, Bedeutungen und Formen von Sauberkeit und Schmutz in verschiedenen urbanen Kontexten. Basierend auf empirischen Forschungen liefert diese Untersuchung neben umfassenden empirischen Daten auch weiterführende theoretische Einsichten zu diesen kulturspezifischen Phänomenen, die über eine dichotome, strukturalistisch geprägte Sichtweise von "sauber" und "schmutzig" hinausweisen.

Re-examining Mary Douglas' work on pollution and concepts of purity, this volume explores modern expressions of these themes in urban areas, examining the intersections of material and cultural pollution. It presents ethnographic case studies from a range of cities affected by globalisation processes such as neoliberal urban policies, privatisation of urban space, continued migration and spatialized ethnic tension. What has changed since the appearance of purity and danger? How have anthropological views on pollution changed accordingly? This volume focuses on cultural meanings and values that are attached to conceptions of "clean" and "dirty", purity and impurity, healthy and unhealthy environments, and addresses the implications of pollution with regard to discrimination, class, urban poverty, social hierarchies and ethnic segregation in cities.
Keywords: Stadtsoziologie; Urbanität; Öffentlicher Raum; Öffentliche Sicherheit; Verschmutzung; Gefahrenabwehr; Sozialgruppe; Armut; Schmutz; Sauberkeit; Soziale Kontrolle; Devianz; Aufenthaltsverbot; Kulturelle Differenz; Städtevergleich